FRI0486 Health-Related Quality of Life in Systemic Sclerosis as Measured by SF-36, EQ-5D and SF-6D: Comparison with a Primary Raynaud Phenomenon and a Selected Sample of Healthy Controls. (9th June 2015) - De Angelis, R.; Ingegnoli, F.; Di Donato, E.; Gualtierotti, R.; Schioppo, T.; Salaffi, F.
Abstract : Background: The health-related quality of life (HRQL) may be variously impaired in systemic sclerosis (SSc) and traditional methods of evaluation, with a focus on skin or musculoskeletal system, may fail to describe the extensive multi-dimensional issues associated to the disease. Objectives: The aim of this study was to compare the HRQL scores of the Medical Outcome Study Short-Term 36 (SF-36) and of two widely used indirect utility instruments, the EuroQol-5D (EQ-5D) and the Short Form-6D (SF-6D), between SSc patients, subjects presenting only a primary Raynaud phenomenon (RP) and no other symptoms, and healthy controls. Methods: A cross-sectional study was carried out among 417 patients (187 with SSc and 230 with primary RP) who were attending two academic outpatient clinics. SSc patients were further subdivided into two groups: patients with limited cutaneous SSc (lcSSc) (137 patients) and patients with diffuse cutaneous SSc (dcSSc) (50 patients), based on the distribution of the skin thickening and on the presence of autoantibodies. 582 healthy controls were used for the comparison. Patients were asked to complete SF-36, SF-6D and EQ-5D. SF-6D utility scores were calculated using the eight mean SF-36 scores, according to published algorithms. The following socio-demographic and clinical variables were included: age, gender, level of education and presence of comorbidities. Demographic and clinical measures were compared using Mann–Whitney U test or Kruskal-Wallis test for continuous variables, and chi-square analysis for discontinuous variables. Standardized difference scores (the s-score or normal score) were also calculated. Results: In comparison to healthy controls, SSc patients showed a significant impairment in all of the eight subscales of the SF-36 (p<0.0001), as well as the physical and mental component summary scores (PCS and MCS) (p<0.0001), and in EQ-5D and SF-6D scores (p<0.0005).There were significant differences between dcSSc and lcSSc: dcSSC patients reported worse health in all SF-36 subscales, with particular emphasis on physical role, bodily pain and social function (p<0.0001) and on emotional role and mental health (p<0.001). Dimensions typically affected by SSc were general health status (s-score -1.47), bodily pain (s-score -1.21), physical function (s-score -0, 80), social function (s-score -0, 79), and physical role (s-score -0, 73) whereas general health status (s-score -0.91), mental health (s-score -0, 64) and bodily pain (s -score -0.55) were the only dimensions significantly impaired in primary RP patients. Conclusions: HRQL of SSc patients was significantly impaired in contrast to primary RP and healthy controls, both in the SF36 physical and mental scores, as well as in EQ-5D and SF-6D scores. The significant differences found between dcSSc and lcSSc are to be emphasized, given the lack of literature on the subject. Further research is required to fully understand the respective role of the different evaluation methods and to examine the implications for estimates of the impact of health care interventions in SSc. References: Gualtierotti R, Scalone L, Ingegnoli F, Cortesi P, Lubatti C, Zeni S, Meroni PL. Health related quality of life assessment in patients with systemic sclerosis. Reumatismo 2010; 62: 210-4. Disclosure of Interest: None declared